Nonlinearity-tailored fiber laser technology for low-noise, ultra-wideband tunable femtosecond light generation - Liu Xiaomin; Laegsgaard Jesper; Egorov R. I. Roman Igorevich; Svane A. S. Ask S.; Ilday F. O. F. Omer; Tu Haohua; Boppart S. A. Stephen A.; Turchinovich D. Dmitry (2017, 2017)
Title screen